Implementation of the Al-Qur'an Literacy Program to Improve the Ability to Read the Al-Qur'an at the Al-Abid Islamic Elementary School in Medan - Siti Nurhalizah; Amiruddin Siahaan; Afrahul Fadhila Daulai (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The research aims to analyze: (1) the Al-Qur'an literacy program (2) the implementation of the Al-Qur'an literacy program (3) the evaluation process for the implementation of Al-Qur'an literacy (4) supporting factors and inhibiting factors for Al-Qur'an literacy 'an. This research was conducted at the Al-Abid Islamic elementary school in Medan Selayang. This research is qualitative analysis research with a descriptive approach. The data source is the wafa Qur'an literacy coordinator and the right brain wafa method book, while the secondary data source is library materials, literature and research first. Data collection instruments are documentation and interviews. Qualitative data analysis techniques include descriptions of material, construction and language aspects, while quantitative analysis of validity, reliability, level of difficulty, distinguishability and distractors. Research findings show: (1) Al-Qur'an literacy program at Al Islamic Private Elementary School -Abid refers to government regulations, in this case Minister of Education and Culture Regulation No. 23 of 2015 as a form of implementing literacy to support the educational process and teaching and learning activities. (2) Implementation of the Al-Qur'an literacy program, using the wafa method, using hijaz tones, using special Wafa books, using a level system, evaluation (3) Evaluation process of the results of implementing Al-Qur'an literacy, carried out every 2 weeks includes daily, weekly and monthly assessments to determine the extent of students' Al-Qur'an literacy results (4) Supporting and inhibiting factors for the Al-Qur'an literacy program, Supporting factors for Al-Qur'an literacy, Continuous method , Good cooperation between teachers and parents of students, Factors inhibiting Al-Qur'an literacy, From teacher factors, lack of time in teaching Al-Qur'an literacy, Students who do not repeat their lessons at home, Short implementation time.